Pengaruh Pembatasan Kekuasaan Presiden Terhadap Praktik Ketatanegaraan Indonesia - Purnomo, Chrisdianto Eko (Mahkamah Konstitusi Republik Indonesia, 2010)
This research effort to search the contents president power restriction in achieving constitutional governmant in Indonesia. The restriction power of president related to restriction of president authority. In other sides restriction of president power can be viewed thorought functional relation among president with House of representative council (DPR), representative people assembly (MPR), Local Representative Council (DPD), and functional relation among president with Supreme of court (MA) and Constitutional Court (MK).The result of research shown that the restriction content of president power can be viewed not only restriction the time of president’s office but also restriction of content presiden authority, i.e restriction to choose state officers and restriction in law making. And restriction of content president power can be viewed in functional president relation with legislative and constitutive institutions.